Evaluation of two different doses of pre-emptive intravenous magnesium sulphate as post operative adjunct analgesia after gynaecological surgery - Tan, HY; Cheah, SK; Azrin MA,; Ooi Su Min, Joanna Su Min (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
This study compared the analgesic effects of pre-emptive intravenous magnesium sulphate of different dosages in patients undergoing lower abdominal gynaecological surgery. Fifty-six patients with Body Mass Index (BMI) <35 kg/m2 who underwent lower abdominal gynaecological surgery were randomly recruited into two groups. Group I received one ampoule (2.47 g) of magnesium sulphate and Group II received 50 mg/kg magnesium sulphate (based on body weight), pre-operatively. Pain score and patient controlled analgesia (PCA) morphine requirement were compared at 30 minutes, 12 hours and 24 hours post-operatively. The pain score was comparable at all intervals between the two groups (30 minutes, p = 0.450; 12 hours, p = 0.402; and 24 hours, p = 1.000). Post-operative PCA morphine requirement was not statistically significant between the two groups at 30 minutes, 12 hours, and 24 hours (2.7 vs 2.4 mg, p = 0.545; 12.5 vs 9.8 mg, p = 0.154; 7.7 vs 6.4 mg, p = 0.323). The side-effects of magnesium sulphate on blood pressure, heart rate and sedation were not statistically significant between the two groups. In conclusion, the analgesic effects of pre-emptively administered intravenous MgSO4 of 2.47 g (one ampule) was comparable to 50 mg/kg in patients with BMI less than 35 kg/m2 following lower abdominal gynaecological surgery under general anaesthesia with negligible side effects.